Monocytes Differentiate to Immune Suppressive Precursors of Metastasis-Associated Macrophages in Mouse Models of Metastatic Breast Cancer - Kitamura, Takanori; Doughty-Shenton, Dahlia; Cassetta, Luca; Fragkogianni, Stamatina; Brownlie, Demi; Kato, Yu; Carragher, Neil; Pollard, Jeffrey W. (Frontiers in Immunology, 2018)
Metastasis-associated macrophages (MAMs) play pivotal roles in breast cancer metastasis by promoting extravasation and survival of metastasizing cancer cells. In a metastatic breast cancer mouse model we previously reported that circulating classical monocytes (C-MOs) preferentially migrated into the tumor-challenged lung where they differentiated into MAMs. However, the fate and characteristics of C-MOs in the metastatic site has not been defined. In this study we identified that adoptively transferred C-MOs (F4/80lowCD11b+Ly6C+) differentiated into a distinct myeloid cell population that is characterized as F4/80highCD11bhighLy6Chigh and gives rise to MAMs (F4/80lowCD11bhighLy6Clow) within 18 hours after migration into the metastatic lung. In mouse models of breast cancer, the CD11bhighLy6Chigh MAM precursor cells (MAMPCs) were commonly found in the metastatic lung, and their accumulation was increased during metastatic tumor growth. The morphology and gene expression profile of MAMPCs were distinct from C-MOs and had greater similarity to MAMs. For example MAMPCs expressed mature macrophage markers such as CD14, CD36, CD64, and CD206 at comparable levels with MAMs, suggesting that MAMPCs have committed to a macrophage lineage in the tumor microenvironment. MAMPCs also expressed higher levels of Arg1, Hmox1, and Stab1 than C-MOs to a comparable level to MAMs. Expression of these MAM associated genes in MAMPCs was reduced by genetic deletion of colony stimulating factor 1 receptor (CSF1R). On the other hand, transient CSF1R blockade did not reduce the number of MAMPCs in the metastatic site, suggesting that CSF1 signaling is active in MAMPCs but is not required for their accumulation. Functionally MAMPCs suppressed the cytotoxicity of activated CD8+ T cells in vitro in part through superoxide production. Overall our results indicate that immediately following migration into the metastatic tumors C-MOs differentiate into immunosuppressive cells that have characteristics of monocytic myeloid-derived suppressor cell (MDSC) phenotype and might be targeted to enhance efficacy of immunotherapy for metastatic breast cancer.